Taylor Series

f(x)=c0+c1(xa)+c2(xa)2+c3(xa)3+c4(xa)4+f(a)=c0+0+0+0+0+c0=f(a)\begin{aligned} f\left( x \right) & = & { c }_{ 0 }+{ c }_{ 1 }{ (x-a) }+{ c }_{ 2 }{ (x-a) }^{ 2 }+{ c }_{ 3 }{ (x-a) }^{ 3 }+{ c }_{ 4 }{ (x-a) }^{ 4 }+\cdots \\ f\left( a \right) & = & { c }_{ 0 }+0+0+0+0+\cdots \\ \Rightarrow { c }_{ 0 } & = & f\left( a \right) \end{aligned}

f(1)(x)=1c1+2c2(xa)+3c3(xa)2+4c4(xa)3+f(1)(a)=1c1+0+0+0+c1=f(1)(a)1\begin{aligned} f^{ (1) }\left( x \right) & = & 1{ c }_{ 1 }+2{ c }_{ 2 }{ (x-a) }+3{ c }_{ 3 }{ (x-a) }^{ 2 }+4{ c }_{ 4 }{ (x-a) }^{ 3 }+\cdots \\ f^{ (1) }\left( a \right) & = & 1{ c }_{ 1 }+0+0+0+\cdots \\ \Rightarrow { c }_{ 1 } & = & \frac { f^{ (1) }\left( a \right) }{ 1 } \end{aligned}

f(2)(x)=(21)c2+(32)c3(xa)+(43)c4(xa)2+f(2)(a)=(21)c2+0+0+c2=f(2)(a)21\begin{aligned} f^{ (2) }\left( x \right) & = & (2\cdot 1){ c }_{ 2 }+(3\cdot 2){ c }_{ 3 }{ (x-a) }+(4\cdot 3){ c }_{ 4 }{ (x-a) }^{ 2 }+\cdots \\ f^{ (2) }\left( a \right) & = & (2\cdot 1){ c }_{ 2 }+0+0+\cdots \\ \Rightarrow { c }_{ 2 } & = & \frac { f^{ (2) }\left( a \right) }{ 2\cdot 1 } \end{aligned}

f(3)(x)=(321)c3+(432)c4(xa)+f(3)(a)=(321)c3+0+c3=f(3)(a)321\begin{aligned} f^{ (3) }\left( x \right) & = & (3\cdot 2\cdot 1){ c }_{ 3 }+(4\cdot 3\cdot 2){ c }_{ 4 }{ (x-a) }+\cdots \\ f^{ (3) }\left( a \right) & = & (3\cdot 2\cdot 1){ c }_{ 3 }+0+\cdots \\ \Rightarrow { c }_{ 3 } & = & \frac { f^{ (3) }\left( a \right) }{ 3\cdot 2\cdot 1 } \end{aligned}

cn=f(n)(a)n!\Longrightarrow { c }_{ n }=\frac { f^{ (n) }\left( a \right) }{ n! }

f(x)=n=0cn(xa)nf(x)=n=0f(n)(a)n!(xa)n\begin{aligned} f\left( x \right) & = & \displaystyle \sum _{ n=0 }^{ \infty }{ { c }_{ n }{ (x-a) }^{ n } } \\ \quad & \Longrightarrow & \boxed { f\left( x \right) =\displaystyle \sum _{ n=0 }^{ \infty }{ \frac { f^{ (n) }\left( a \right) }{ n! } { (x-a) }^{ n } } } \end{aligned}

Note by Gordon Chan
2 weeks, 6 days ago

No vote yet
1 vote

</code>...<code></code> ... <code>.">   Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in </span>...<span></span> ... <span> or </span>...<span></span> ... <span> to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Sort by:

Top Newest

@Gordon Chan If you have just learnt about this, then here's an interesting question.......How would you find the Taylor expansion of cotx\displaystyle \cot x centered at x=0\displaystyle x=0

Aaghaz Mahajan - 2 weeks, 5 days ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...